(untitled) (Proceedings of the World Conference on Waste Management, 2019)
Organic waste (including kitchen, garden/lawn, and agricultural waste) were subject to composting through static pile and soil pit composting techniques to determine the best method for managing the organic fraction of Municipal Solid Waste (MSW). These conventional methods were used with some innovations (by using soil as seed compost and aeration assembly) to increase the efficiency while keeping the process cost effective. Quantitative parameter analysis of initial feedstocks such as weight, moisture content (MC) and bulk density (BD) were measured before setting up each experiment. Temperature variation was monitored on a daily basis and measurement of CO2 emission on weekly basis. Moreover, mixing of feedstock for aeration and applying water for optimum moisture content were also subject to weekly activities. Final compost from each experiment was analyzed against physical and chemical parameters such as colour, MC, BD, water holding capacity, pH and electrical conductivity. Aerobic soil pit showed better results among other composting techniques with with BD of 530±0.01 kg/m3 , MC 37.40±0.26 %, water holding capacity 94±0.45 %, pH 8.00±0.10 and electrical conductivity 1.06±14.42 dS/m. Based on the experiment’s results, there were two conclusions drawn, first the application of soil proved to be very helpful as seed compost in a static pile showing good results. Secondly, soil pit composting with modification of passive aeration also proved it as a potential technique to manage organic waste.